EMOTIONAL INTELLIGENCE AND EATING DISORDERS: Comparison by Gender in Taekwondo Athletes - Galuh Puji Astuti, - (IKIP Budi Utomo Malang, 2023)
Emotional intelligence is necessary to manage emotions and feelings to have a positive impact on mental health. This study examines emotional intelligence and eating disorders in taekwondo athletes. The purpose of this study was to determine the relationship between emotional intelligence and eating disorders with mental health disorders in taekwondo athletes and to provide gender-specific comparisons. A quantitative sample of 29 taekwondo athletes aged 13-17 was used as a research method. The Trait Emotional Intelligence Adolescent Short Form model was used to measure emotional intelligence and the EAT-26 model was used to measure eating disorders. The data analysis technique uses a correlation test. Based on data processing and analysis using SPSS, the results show a relationship between emotional intelligence and eating disorders in 13-17-year-old male taekwondo athletes, and there was no relationship between emotional intelligence and eating disorders in female taekwondo athletes. The conclusion of this research is that there is a negative and significant relationship between emotional intelligence and eating disorders in adolescent taekwondo athletes. Kecerdasan emosional diperlukan untuk mengendalikan perasaan dan emosi sehingga dapat memberikan dampak positif pada kesehatan mental. Penelitian ini bertujuan untuk mendapati hubungan antara kecerdasan emosi dan gangguan makan sebagai salah satu gangguan mental pada atlet taekwondo dan memberikan perbandingan berdasarkan jenis kelamin. Metode penelitian yang digunakan adalah metode penelitian kuantitatif dengan sampel sebanyak 29 atlet taekwondo berusia 13-17 tahun. Instrumen penelitian yang digunakan adalah Trait Emotional Intelligence Adolescent Short Form untuk mengukur kecerdasan emosional dan Eating Attitude Test-26 untuk mengukur gangguan makan. Tenik analisis data menggunakan uji korelasi. Berdasarkan pengolahan dan analisis data dengan menggunakan SPSS, hasil yang diperoleh memperlihatkan bahwa terdapat hubungan antara kecerdasan emosional dengan gangguan makan pada atlet taekwondo laki-laki usia 13-17 tahun dan tidak ada hubungan antara kecerdasan emosional dan gangguan makan pada atlet taekwondo perempuan. Kesimpulan dari penelitian ini adalah terdapat hubungan negatif dan signifikan antara kecerdasan emosional dan gangguan makan pada atlet taekwondo usia remaja.